Flavonol and A-type procyanidin-rich extracts of Prunus spinosa L. flower exhibit anticoagulant activity through direct thrombin inhibition, but do not affect platelet aggregation in vitro - Marchelak, Anna; Kolodziejczyk-Czepas, Joanna; Ponczek, Michał B.; Liudvytska, Oleksandra; Markowicz-Piasecka, Magdalena; Bielska, Beata; Miłowska, Katarzyna; Olszewska, Monika A. (Frontiers in Pharmacology, 2023)
Background: Blackthorn flower (Prunus spinosa L.) is a traditional herbal remedy recommended for treating cardiovascular diseases (CVDs). Aim: This in vitro study investigates the effects of flavonol and A-type procyanidin-rich blackthorn flower extracts on the hemostatic system, including the blood plasma coagulation cascade and platelet aggregation. Methods: Six distinct extracts, characterized through various techniques, including LC-MS/MS, were assessed at in vivo-relevant levels (1-50 μg/mL) for their antithrombotic activity. The thrombin, prothrombin, and activated partial thromboplastin times were measured. Additionally, the thrombin enzymatic activity was tested using the chromogenic substrate S-2238 and fibrinogen as the physiological substrate of the enzyme. To gain insights into the mechanism of action, the interactions between the primary extracts' constituents, their potential metabolites, and thrombin were examined in silico. The computational analyses were complemented by in vitro experiments and circular dichroism spectroscopy. The platelet aggregation in human platelet-rich plasma was assessed after ADP or collagen stimulation. Furthermore, the extracts' biocompatibility was tested on human peripheral blood mononuclear cells (PBMCs) and red blood cells (RBCs). Results: The extracts slightly prolonged the prothrombin and thrombin times and effectively inhibited the thrombin's enzymatic activity, reducing its amidolytic and proteolytic functions at 50 μg/mL by 91.2% and 74.8%, respectively. In silico molecular docking demonstrated a strong binding affinity of the examined polyphenols and their metabolites to thrombin. Most analytes bound exclusively within the enzyme active site; however, afzelin, kaempferitrin, and procyanidin A2 revealed the affinity to additional binding sites, including exosite I. The structure-activity relationship of flavonols as thrombin inhibitors was studied in vitro. Circular dichroism spectroscopy confirmed that the interactions between thrombin and the compounds (even at 1 μg/mL) induce alterations within the α-helices' secondary structure, resulting in noticeable changes in the enzyme's CD spectrum. On the other hand, the extracts did not influence platelet aggregation. Eventually, their cellular biocompatibility with PBMCs and RBCs was confirmed. Conclusions: The extracts directly inhibit thrombin, a critical serine protease in hemostasis and a prime anticoagulant drug target, and do not exhibit antiplatelet effects. This study enhances the knowledge of the biological activity of blackthorn flowers and supports their traditional use in CVDs.